Optimasi Proses Produksi Beton Ready Mix untuk Meminimalisir Waste pada Material di Batching Plant PT. X Gorontalo dengan Metode Lean Manufacturing - Bone, Kurniawan; Uloli , Hendra; Simatupang, Rudolf (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In the manufacturing industry, a company's productivity can be seen from its ability to run production processes effectively and efficiently. The problem of inefficient production occurs in the production process, which makes the production time longer and does not meet the targets. This forces operators to work overtime, and the company has to incur additional costs for the overtime operators. This research aims to identify waste and the impacts that affect production cost losses. Several waste factors that have a dominant impact on production cost losses have been identified. The result of this study is a change in the cycle time from before the improvement, which was 21,600 seconds or 360 minutes. After improvements were made to activities that caused waste, the cycle time of the ready-mix concrete production process became 18,600 seconds or 310 minutes.